Grounding Global Climate Change: Contributions from the Social and Cultural Sciences - Greschke, Heike; Tischler, Julia (Springer Netherlands Imprint: Springer, 2015)
Introduction: grounding global climate change -- Part I: Interdisciplinarity, climate research and the role of the social sciences -- Ecological novelty: towards an interdisciplinary understanding of ecological change in the Anthropocene -- Predicting the past? Integrating climate and culture during historical famines -- Anthropology in the Anthropocene: sustainable development, climate change and interdisciplinary research -- Part II: Searching for the social facts of global climate change: ethnographic perspectives -- Climate and mobility in the West African Sahel: conceptualising the local dimensions of the environment and migration nexus -- Animal belongings: human-non human interactions and climate change in the Canadian Subarctic -- Part III: Spinning global webs of local knowledges: collaborative and comparative ethnographies -- The social facts of climate change: an ethnographic approach -- Comparing climate worlds: theorising across ethnographic fields -- Towards imagining the big picture and the finer details: exploring global applications of a local and scientific knowledge exchange methodology -- Part IV: Concluding statement -- You ain’t seen nothing yet: a death-defying look at the future of the climate debate.
Includes bibliographical references at the end of each chapters
Keywords: Klimaänderung